Observational Study of the association of GGT with Benign and Malignant Breast Tumors: Observational Study of the association of GGT with Benign and Malignant Breast Tumors - Meena, Pratibha; Totade, Sanjay; Meena, Shailendra (National Journal of Integrated Research in Medicine, 2018)
Background: Gamma-glutamyltransferase (GGT) is a cell surface enzyme that uniquely enables glutathione catabolism by hydrolysing the gamma glutamyl bond between glutamate and cysteine. GGT is one of the enzymes which may rise in malignancies and since being economic and relatively easier to determine, remain as useful and practical marker in terms of prognosis and also early diagnosis. Breast cancer is a major public health issue in India. Most cases of Breast cancer in India are diagnosed at advanced stage, and outcome is not as good as earlier stages, most important reason being lack of screening and awareness. The objective of present study was to assess the clinical utility of serum levels of GGT in cases of breast lesions and to evaluate whether their levels are significantly higher in cases of breast malignancies as compared to cases of benign breast lesions. Methods: A total number of 160 subjects were studied, comprising of 80 cases of benign breast lesions and 80 Breast cancer subjects. Breast cancer subjects were further divided depending on stage of the cancer. Serum level of GGT was estimated in all subjects. Results: The present observational study has shown a significant elevation in serum levels of GGT in cases of carcinoma Breast as compared to benign breast lesions. These levels raised significantly with severity (stage) of carcinoma Breast. Conclusion: This study concludes that enzyme markers like serum GGT could serve as cost effective biomarkers for carcinoma breast and help in early detection of progression of the disease. [Pratibha M NJIRM 2017; 8(4):53-57]